Changes in Alternative Splicing in Response to Domestication and Polyploidization in Wheat . Issue 4 (13th October 2020) - Yu, Kuohai; Feng, Man; Yang, Guanghui; Sun, Lv; Qin, Zhen; Cao, Jie; Wen, Jingjing; Li, Haoran; Zhou, Yan; Chen, Xiangping; Peng, Huiru; Yao, Yingyin; et al.
Abstract : Transcriptomic analyses of several wheat species with different ploidies reveal alternative splicing changes in response to wheat domestication or polyploidization. Abstract: Alternative splicing (AS) occurs extensively in eukaryotes as an important mechanism for regulating transcriptome complexity and proteome diversity, but variation in the AS landscape in response to domestication and polyploidization in crops is unclear. Hexaploid wheat (AABBDD, Triticum aestivum ) has undergone two separate allopolyploidization events, providing an ideal model for studying AS changes during domestication and polyploidization events. In this study, we performed high-throughput transcriptome sequencing of roots and leaves from wheat species with varied ploidies, including wild diploids (A b A b, Triticum boeoticum ) and tetraploids (AABB, Triticum dicoccoides ), domesticated diploids (A m A m, Triticum monococcum ) and tetraploids (AABB, Triticum dicoccum ), hexaploid wheat (AABBDD, T . aestivum ), as well as newly synthesized hexaploids together with their parents. Approximately 22.1% of genes exhibited AS, with the major AS type being intron retention. The number of AS events decreased after domestication in both diploids and tetraploids. Moreover, the frequency of AS occurrence tended to decrease after polyploidization, consistent with the functional sharing model that proposes AS and duplicated genes are complementary in regulating transcriptome plasticity in polyploid crops. In addition, the subgenomes exhibited biased AS responses to polyploidization, and ∼87.1% of homeologs showed AS partitioning in hexaploid wheat. Interestingly, substitution of the D-subgenome modified 42.8% of AS patterns of the A- and B-subgenomes, indicating subgenome interplay reprograms AS profiles at a genome-wide level, although the causal–consequence relationship requires further study. Conclusively, our study shows that AS variation occurs extensively after polyploidization and domestication in wheat species.